Evaluation of human coronary vasodilator function predicts future coronary atheroma progression. Issue 17 (1st March 2018) - Sidharta, Samuel L; Baillie, Timothy J; Howell, Stuart; Nicholls, Stephen J; Montarello, Natalie; Honda, Satoshi; Shishikura, Daisuke; Delacroix, Sinny; Kim, Susan; Beltrame, John F; Psaltis, Peter J; Worthley, Stephen G; et al.
Abstract : Objective: Coronary vasodilator function and atherosclerotic plaque progression have both been shown to be associated with adverse cardiovascular events. However, the relationship between these factors and the lipid burden of coronary plaque remains unknown. These experiments focus on investigating the relationship between impaired coronary vasodilator function (endothelium dependent (salbutamol) and endothelium independent (glyceryl trinitrate)) and the natural history of atheroma plaque progression and lipid burden using dual modality intravascular ultrasound (IVUS) and near-infrared spectroscopy (NIRS) imaging. Methods: 33 patients with stable chest pain or acute coronary syndrome underwent serial assessment of coronary vasodilator function and intracoronary plaque IVUS and NIRS imaging. Coronary segmental macrovascular response (% change segmental lumen volume (ΔSLV)), plaque burden (per cent atheroma volume (PAV)), lipid core (lipid-rich plaque (LRP) and lipid core burden index (LCBI)) were measured at baseline and after an interval of 12–18 months (n=520 segments). Results: Lipid-negative coronary segments which develop into LRP over the study time period demonstrated impaired endothelial-dependent function (−0.24±2.96 vs 5.60±1.47%, P=0.04) and endothelial-independent function (13.91±4.45 vs 21.19±3.19%, P=0.036), at baseline. By multivariate analysis, endothelial-dependent function predicted ∆LCBI (β coefficient: −3.03, 95% CI (−5.81 to −0.25), P=0.033) whereas endothelial-independent function predicted ∆PAV (β coefficient: 0.07, 95% CI (0.04 to 0.10), P<0.0001). Conclusions: Epicardial coronary vasodilator function is a determinant of future atheroma progression and composition irrespective of the nature of clinical presentation. Trial registration number: ACTRN12612000594820, Post-results.